A socio-legal history of the laws of war : constraining carnage - Mullins, Christopher W. (Emerald Publishing Limited, 2023)
Since the Second World War, international laws governing the conduct of war and the behaviour of soldiers on the field of battle have been of strong academic and legal interest. Yet while they have seen their strongest articulation and enforcement in the contemporary era, rules governing such conduct are deeply rooted in human history. Beginning with the origins of organized warfare in the ancient world, A Socio-Legal History of the Laws of War: Constraining Carnage traces key structural and cultural changes through multiple historical contexts, highlighting various approaches to the nature and purpose of war, as well as the roles of both bystanders and participants. Where other scholarship has focused on the legality of war itself, Christopher W. Mullins concentrates on rules surrounding the behaviour of soldiers and commanders in the field while also demonstrating how these issues have transformed over time. Rooted in critical historical documents from the Tudors to the American Revolution, this rich history, the first of two volumes, provides a cogent understanding of how the current historical moment has developed, as well as of the potential paths that lie ahead.
Keywords: War (International law); War (International law) -- History.; War (International law) -- Social aspects.; Social Science -- Criminology.; Other warfare & defence issues.; elektronické knihy; electronic books